Território, memórias, vidas e histórias da comunidade de São João Batista no rio Tucumandubazinho em Abaetetuba-PA - CARVALHO, Gleiciane do Rosário Farias (2022)
The present work had as general objective to understand how the history, life, identity and territory of the Community of São João Batista on the Tucumandubazinho River in Abaetetuba/PA was constituted. The methodology of the work was based on qualitative research, with a study in oral history. As a result, the following sectinos were scored: 1Reflecting memories, territory and identity of the sujects of the field. We sought to approach the history of the São João Batista community, Rio Tucumandubazinho through the memory of its sujects; 2-São João Batista Community in the eyes of the subjects of the Waters. The territory and life of the community, its practices and experiences of the daily work of the community were highlighted; 3:RESISTANCE and RIGHTS-Memory of the struggle of the Extractive Settlement Program (PAE-Bacuri Island). The dynamics of the settlement’s struggle and resistance were highligted. The research results showed that the social, cultural, identity aspects, and the way of life, work and culture of the community have been maintained from generation to generation, although the world is in constant transformation and the suject can modify and even change of thought and life.